RANCANGAN SISTEM KOMPUTER VISI UNTUK MENDETEKSI PARASIT ICHTHYOPHTHIRIUS MULTIFILIIS PADA IKAN AIR TAWAR - Achmad Taufan; Aulia Putri Sakinah; Kevin Yohanes Suwito; Utomo Tri Hantoro; Marliza Ganefi Gumay (Jurusan Teknik Informatika, 2015)
Limitations of food in Indonesia demand the perpetrators of animal farming business to meet the needs of the community. One of the important food is freshwater fish. Besides the price is more affordable than saltwater fish, quite a lot of entrepreneurs engaged in the cultivation of freshwater fish. But often the fish harvest did not meet the expectations of employers fishponds due to various factors, one of which is a deadly disease in fish. The most common diseases are 'white spot' caused by the protozoan Ichthyophthirius multifiliis, which only affects freshwater fish. This parasite attached to the body of the fish and looks like white spots with size ± 1 mm. 'White spot' can cause irritation and holes in the body of the fish, causing stress, difficulty breathing and swimming until can cause death. If not detected early, the parasites 'Ich' can spread to the entire pond. The design of a computer vision system is intended to create a system that can detect the disease as early as possible 'white spots' without relying on human vision that is not capable of overseeing 24 hours. In this design the identification is done by detection feature and image comparison.